Reforming retirement age in DB and DC pension systems in an aging OLG economy with heterogenous agents - Joanna Tyrowicz; Krzysztof Makarski; Marcin Bielecki (IZA Journal of Labor Policy, 2016)
We analyze the effects of increasing the retirement age in two economies with overlapping generations and within cohort ex ante heterogeneity. The first economy has a defined benefit system, and the second economy is in transition from a defined benefit to a defined contribution. We find that if increase in the retirement age is phased in a way that allows agents to adjust, welfare is not reduced and welfare effects have a similar magnitude and between-cohort distribution in both types of the pension systems.
Keywords: C60; C68; D63; E17; E21; H55; 330; Retirement age; DB; DC; Pension system reform; Longevity